La colonización y el asentamiento del norte del Perú: innovación, tecnología y adaptación en el valle de Zaña - Rossen, Jack (Pontificia Universidad Católica del Perú, 2012)
Northern Perú’s Colonization and Settlement: Innovation, Technology and Adaptation at Zaña ValleyThis paper discusses the archaeological and paleoecological data for the first people to enter the Zaña Valley and their later development as sedentary horticulturalists. The technical, social and economic implications of these developments in regard to forming the foundations of early Andean civilization are also presented for the Early (ca. 10,000-7500 b.p.) and Middle (ca. 7500-5000 b.p.) Preceramic Periods. We discuss the Paijan, Nanchoc, Pircas and Tierra Blanca cultures in terms of their settlement patterns, bifacial and unifacial lithic technologies, economies, and social organization. The most important site complex is the Nanchoc Mound site, dated between 7200-5000 years ago, where lime seems to have been produced in a separate ritual space for consumption with coca leaves. The broader implications of these cultural transformations are discussed with respect to the importance of the Middle Preceramic Period for understanding the beginnings of central Andean civilization.